Teaching OCL Standard Library: First Part of an OCL 2.x Course - Chimiak-Opoka, Joanna; Demuth, Birgit (Electronic Communications of the EASST, 2011)
Our aim is to provide a complete set of materials to teach OCL. They can be used in bachelor or master programs of computer science curricula and for training in an industrial context. In this paper we present the first part of the course related to the OCL Standard Library. This part provides model independent examples to teach OCL types and their operations. It enables users to gain a basic understanding of the OCL Standard Library, which can be used as a starting point to write model constraints (OCL specifications) or model queries. Additionally, to the content of the paper, we provide a set of OCL packages, exercise proposals and lecture slides.